Physicochemical characterization and cytotoxicity of articaine-2-hydroxypropyl-β-cyclodextrin inclusion complex - Burga-Sánchez, Jonny; Ferreira, Luiz Eduardo Nunes; Volpato, Maria Cristina; Cabeça, Luis Fernando; Braga, Mario; Fraceto, Leonardo Fernandes [UNESP]; de Paula, Eneida; Groppo, Francisco Carlos (My University, 2020)
Articaine (ATC) is one of the most widely used local anesthetics in dentistry. Despite its safety, local toxicity has been reported. This study aimed to develop an ATC-2- hydroxypropyl-β-cyclodextrin inclusion complex (ATC HPβCD) and to assess its toxicity in vitro. The inclusion complex was performed by solubilization, followed by a fluorimetric and job plot assay to determine the complex stoichiometry. Scanning electron microscopy, DOSY- 1 H-NMR, differential scanning calorimetry (DSC), and sustained release kinetics were used to confirm the inclusion complex formation. In vitro cytotoxicity was analyzed by MTT assay and immunofluorescence in HGF cells. Fluorimetric and job plot assay determined the inclusion complex stoichiometry (ATC:HPβCD = 1:1) and complex formation time (400 min), as indicated by a strong host/guest interaction (Ka = 117.8 M − 1), complexed fraction (f = 41.4%), and different ATC and ATC HPβCD melting points (172 °C e 235 °C, respectively). The mean of cell viability was 31.87% and 63.17% for 20-mM ATC and 20-mM ATC HPβCD, respectively. Moreover, remarkable cell toxicity was observed with free ATC by immunofluorescence. These results indicate the ATC HPβCD complex could be used to improve the safety of ATC. Further research are needed to establish the anesthetic safety and effectiveness in vivo.
Keywords: Articaine; Cell viability; Human gingival fibroblast; Hydroxypropyl-β-cyclodextrin